Lab-on-Chip Platform for Culturing and Dynamic Evaluation of Cells Development - Podwin, Agnieszka (Micromachines (Basel), 2020)
This paper presents a full-featured microfluidic platform ensuring long-term culturing and behavioral analysis of the radically different biological micro-objects. The platform uses all-glass lab-chips and MEMS-based components providing dedicated micro-aquatic habitats for the cells, as well as their intentional disturbances on-chip. Specially developed software was implemented to characterize the micro-objects metrologically in terms of population growth and cells’ size, shape, or migration activity. To date, the platform has been successfully applied for the culturing of freshwater microorganisms, fungi, cancer cells, and animal oocytes, showing their notable population growth, high mobility, and taxis mechanisms. For instance, circa 100% expansion of porcine oocytes cells, as well as nearly five-fold increase in E. gracilis population, has been achieved. These results are a good base to conduct further research on the platform versatile applications.